2021
DOI: 10.1016/j.mbplus.2021.100071
|View full text |Cite
|
Sign up to set email alerts
|

BMP antagonists in tissue development and disease

Abstract: Bone morphogenic proteins (BMPs) are important growth regulators in embryogenesis and postnatal homeostasis. Their tight regulation is crucial for successful embryonic development as well as tissue homeostasis in the adult organism. BMP inhibition by natural extracellular biologic antagonists represents the most intensively studied mechanistic concept of BMP growth factor regulation. It was shown to be critical for numerous developmental programs, including germ layer specification and spatiotemporal gradients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 115 publications
(168 reference statements)
0
24
0
1
Order By: Relevance
“…The BMP-9/10 group binds to ALK1 and binds weakly to ALK2. BMP signaling is modified by membrane proteins, as well as by diverse secreted proteins ( Brazil et al, 2015 ; Correns et al, 2021 ). A co-receptor, endoglin (also known as CD105) upregulates BMP-9/10-ALK1 signaling in endothelial cells and downregulates TGF-β-ALK5 signaling ( Dallas et al, 2008 ).…”
Section: Bone Morphogenetic Protein Signaling Pathwaymentioning
confidence: 99%
“…The BMP-9/10 group binds to ALK1 and binds weakly to ALK2. BMP signaling is modified by membrane proteins, as well as by diverse secreted proteins ( Brazil et al, 2015 ; Correns et al, 2021 ). A co-receptor, endoglin (also known as CD105) upregulates BMP-9/10-ALK1 signaling in endothelial cells and downregulates TGF-β-ALK5 signaling ( Dallas et al, 2008 ).…”
Section: Bone Morphogenetic Protein Signaling Pathwaymentioning
confidence: 99%
“…[35][36][37][38] The inability to inhibit BMP through Noggin has important consequences in canonical and non-canonical signaling pathways that can lead to multiple phenotypic diseases as well as uncontrolled cell proliferation and eventual cancer progression. 30 Cell signaling, especially in the TGF-β superfamily of proteins, is highly complex and since Noggin is a key inhibitor of these pathways, 13 it is important to consider its functional mechanisms to understand diseases and its targetability for therapeutic approaches. In our study, we presented the biophysical solution characteristics of Noggin and observed its interaction with heparin ligands.…”
Section: Mutations In the Heparin Binding Site Of Noggin Are Associat...mentioning
confidence: 99%
“…Noggin, which is a glycoprotein secreted into the extracellular matrix has multiple Cardin–Weintraub motifs that bind HS to presumably assist in its correct localization 12,13 . Hence, Noggin is classified as an HS binding protein (HSBP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of selection pressure analyses, it was found that BMP1 in lizards and SH2B3 in snakes were not only genes that were significantly positively selected along the branches of large-bodied species, but also genes that were significantly negatively correlated with body length and body mass. BMPs are important growth regulators of embryogenesis and tissue homeostasis in the adult organism (Correns et al, 2021). Osteogenesis imperfecta (OI) is an inherited bone disease caused by gene mutations characterized by increased bone fragility and recurrent fractures, and more than 20 causative genes including BMP1 have been identified so far (Correns et al, 2021).…”
Section: The Relationship Between Phenotypes and Body-size-related Genesmentioning
confidence: 99%